Dual relational embeddedness and knowledge transfer in European multinational corporations and subsidiaries. Issue 3 (16th May 2018) - Ferraris, Alberto; Santoro, Gabriele; Scuotto, Veronica
Abstract : Purpose: This paper aims to investigate the relationship between the level of subsidiaries' internal and external relational embeddedness and the degree of subsidiaries' knowledge transfer. More specifically, the aim is to explore dual embeddedness of subsidiaries involved in the knowledge transfer process within multinational corporations' (MNCs) network. Design/methodology/approach: The authors empirically analyse 165 European subsidiaries to demonstrate the crucial role of dual relational embeddedness in the transfer of knowledge within MNCs. Data were collected via a close-ended questionnaire and processed through an ordinary least squares regression model. Findings: Results show that internal embeddedness directly and positively influences the degree of subsidiaries' knowledge transfer, whereas external embeddedness does not. Notwithstanding, a higher level of both types of embeddedness – known as dual embeddedness – generates multiplicative and positive effects on the degree of subsidiaries' knowledge transfer. Practical implications: Best practices and relevant knowledge follow a reverse transfer of knowledge from the subsidiaries to the internal MNC network that is facilitated by the relational embeddedness of subsidiaries. This has resulted in developing a dual embeddedness, which introduces new routines and scripts, as well as more relational links. Originality/value: The research emphasises the relevance of the knowledge transfer process in multiple directions, evoking the central role of dual-embedded subsidiaries.